Density dependence mediates the ecological impact of an invasive fish. Issue 7 (22nd April 2020) - DeRoy, Emma M.; Scott, Ryan; Hussey, Nigel E.; MacIsaac, Hugh J.
Abstract: Aim: The way in which habitat heterogeneity and predator density affect predator–prey dynamics, space use and prey risk are understudied aspects of foraging ecology, particularly for invasive species. Likewise, how an invasive species' impact scales with its abundance is poorly understood. We used a model invasive species—lionfish ( Pterois volitans )—to understand emergent multiple predator effects and influences of habitat heterogeneity on consumption rate and prey mortality risk. Location: Florida, USA. Methods: We considered effects of both predator and prey abundance on density‐dependent impact. We used functional response methodology to quantify the per‐capita effect of P. volitans, assessing concomitant influences of prey refuge (3 levels) and predator density (3 levels) on predator–prey space use and predation efficiency across increasing prey densities (7 levels). We then assessed intraspecific interaction outcomes by comparing observed per‐capita effects with predicted estimates based on consumption rates of individual predators. This allowed us to detect the presence of emergent multiple predator effects (MPEs) and tease apart density‐dependent impacts. Results: Lionfish predatory impact was mediated by predator and prey density but unaffected by refugia. Despite incongruent patch preferences between predators and their prey, predator impacts were context‐independent. We also detected nonlinear scaling of impact with increasing predator abundance. Pairs of lionfish had the greatest per‐capita effect, whose cumulative impact on prey matched that expected of independently foraging predators. At the highest predator density (four fish), antagonistic multiple predator effects precipitated prey risk reduction, in which we observed the lowest per‐capita effect. Across predator abundances, prey mortality rates were inversely density‐dependent. Main conclusions: Quantifying non‐independent consumptive effects of multiple conspecific predators across levels of prey abundance can inform better prediction and understanding of invasive species' density‐dependent effects. Additionally, consideration of heterogeneity‐mediated FRs and predator–prey spatial distributions may facilitate more precise and realistic predictions of invader impact across their invaded range.